Resilience and intentions of fishermen transitioning to ecological farming: insights from China's Yangtze River basin - Wang, Xueming; Zheng, Jianming; Yang, Yang; Chen, Tinggui (Frontiers in Environmental Economics, 2025)
IntroductionTo ensure the protection of aquatic ecosystems and fishery resources, while establishing a sustainable mechanism for the transformation of livelihoods that emphasizes ecological farming (leveraging the principles of ecological coupling and symbiosis to achieve harmonious integration between cultivation and breeding), a three-dimensional framework of buffering, self-organization, and learning has been developed based on the theory of “livelihood resilience.” “Resilience” encapsulates the ability of fishing communities (or individuals) to withstand disturbances (buffering), reconfigure themselves (self-organization), and adapt or enhance their circumstances through experiential learning (learning abilities).MethodsThe study examines the extent of livelihood resilience in relation to fishing ban, as well as the readiness of various types of fishermen to embrace ecological farming under different incentive structures. It also simulates the varying willingness to adopt ecological farming across diverse environmental contexts within China.ResultsThe results indicate that: (1) Self-organization ability, particularly the emphasis on subsidy benefits and policy awareness, could independently lead to interpretive outcomes. (2) There are three pathways that can motivate fishermen to adopt ecological farming: self-organization-dominant, self-organization-learning driven, and buffering-learning driven. Concurrently, there are three categories of factors that impede the enhancement of fishermen's willingness to engage in ecological farming: learning inhibition, self-organization-learning inhibition, and buffering-self-organization inhibition. (3) Under specific conditions, self-organization ability can be substituted by the conditional combination of the other two abilities to bolster the willingness of fishermen to adopt, in a manner akin to “all paths leading to the same destination.” (4) Heterogeneity analysis demonstrates that livelihood resilience exerts a more significant influence on the willingness of fishermen in the Yangtze River Basin to participate in ecological farming, particularly in areas with lower economic development levels. Moreover, this resilience has a more pronounced effect on the intentions of older generations.DiscussionThis study offers a novel theoretical framework applicable to ecological farming practices for retired fishermen, operating within a livelihood resilience scale, accompanied by regional heterogeneity support and theoretical guidance for the promotion of sustainable livelihoods.